2013
DOI: 10.1371/journal.pone.0066049
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in Fungal Endophyte Communities Isolated from Cultivated Cotton (Gossypium hirsutum)

Abstract: Studies of fungi in upland cotton (Gossypium hirsutum) cultivated in the United States have largely focused on monitoring and controlling plant pathogens. Given increasing interest in asymptomatic fungal endophytes as potential biological control agents, surveys are needed to better characterize their diversity, distribution patterns and possible applications in integrated pest management. We sampled multiple varieties of cotton in Texas, USA and tested for temporal and spatial variation in fungal endophyte di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 63 publications
2
46
1
Order By: Relevance
“…A recent study which sampled the endophyte diversity in the above-ground tissues of cotton from several populations found a very diverse group, but with relatively few Penicillium (Ek-Ramos et al 2013). Fungal diversity was also high in a review of the endophytes in grass species, with some assemblage similarity to ours (Sánchez Márquez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study which sampled the endophyte diversity in the above-ground tissues of cotton from several populations found a very diverse group, but with relatively few Penicillium (Ek-Ramos et al 2013). Fungal diversity was also high in a review of the endophytes in grass species, with some assemblage similarity to ours (Sánchez Márquez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, DNA-based studies of endophytic organisms isolated from the wild and cultivated plant systems have led to an increasing level of awareness of the high phylogenetic diversity within fungal endophytes (Andrade-Linares et al 2011; Sánchez Márquez et al 2012; Ek-Ramos et al 2013). Some of these endophytes are localised to specific tissue types and some are found systemically.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the EFC of cultivable host plants have shown variability among these communities based on the regions in which the plants are cultivated [37], [38]; however, the variability in EFC among management systems is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…in Ek‐Ramos et al . () and subsequently misidentified as Purpureocillium lilacinum in Lopez et al . () and Lopez & Sword ().…”
Section: Methodsmentioning
confidence: 99%
“…Fungi associated with cotton have been most intensively studied in the context of mycorrhizal interactions and as pathogens (Nehl & McGee, ; Bell et al ., ). Published surveys explicitly aimed at characterizing fungal endophyte diversity in asymptomatic cotton exist, but are relatively rare (e.g., Australia: McGee, ; Wang et al ., ; the United States: Palmateer et al ., ; Ek‐Ramos et al ., ; and Brazil: de Souza Vieira et al ., ). Here we show that manipulating the presence of two strains of fungi that can colonize cotton as an endophyte, Phialemonium inflatum and Beauveria bassana , affects the host plant selection behavior of two key generalist hemipteran sucking bug pests, the western tarnished plant bug ( Lygus hesperus [Miridae] and the southern green stinkbug Nezara viridula [Pentatomidae]) under both no‐choice and choice conditions.…”
Section: Introductionmentioning
confidence: 99%